Planeación financiera en la empresa Auto Repuestos A y D de la ciudad de Loja, período 2016 – 2020. - Sarango Alvarez, Susana Gabriela (2017)
This dissertation called Financial Planning in the company AUTO REPUESTOS AYD of the city of Loja, period 2016 - 2020, was carried out in accordance with the stipulations of the Rules of Academic Regime of the National University of Loja, with the purpose of contributing Effective way and pertinent to the owner of the company to improve the management of resources and thus to increase the profitability of his company, and for it was done based on the objectives set out the same that were fulfilled at the end of the entire process of Financial planning applied to the company. Among the specific objectives we first have to prepare the forecast of inflows and outflows of cash to know the needs of the company and to be able to efficiently handle the resources, for it was necessary to collect sales and historical purchases of economic activity. The second specific objective was the budget of the cash for the fulfillment of the same one went to the elaboration of the programs of inflows and outflows of the same ones that support the budget of the cash, where it was verified that the company will obtain liquidity to be able to invest. Subsequently, it presents the profit planning, which included the preparation of pro forma financial statements, in compliance with the last 5 specific objective, where the pro forma statement of results was structured based on the forecasts of sales and purchases; And the summary of inflows and outflows of cash, obtaining profit in the projected five years. For the determination of the balance sheet it was necessary to apply the percentage of sales method. The methodology used was the percentage of sales method that allowed to fulfill the objectives set. At the end of the thesis are presented the conclusions and recommendations that will help as suggestions to the owner of the company and his accountant to make decisions and achieve the optimization of resources. The most relevant conclusion was that the projected financial statements were prepared and it is determined that, as revenues and expenses increase, asset, liability and equity accounts also increase relative to the established percentages; Also it is observed that the company will have utility in the projected five years the same one that helps the owner to offer different brands of spare parts, also we have its recommendation that is to realize projections feasible to the reality in which the company is found so that The owner can make appropriate decisions for the good performance of his economic activities.